High Time Resolution Analysis of Voltage-Dependent and Voltage-Independent Calcium Sparks in Frog Skeletal Muscle Fibers - Cserne Szappanos, Henrietta; Vincze, János; Bodnár, Dóra; Dienes, Beatrix; Schneider, Martin F.; Csernoch, László; Szentesi, Péter (Frontiers in Physiology, 2020)
In amphibian skeletal muscle calcium (Ca2+) sparks occur both as voltage-dependent and voltage-independent ligand-activated release events. However, whether their properties and their origin show similarities are still in debate. Elevated K+, constant Cl- content solutions were used to initiate small depolarizations of the resting membrane potential to activate dihydropyridine receptors (DHPR) and caffeine to open ryanodine receptors (RYR) on intact fibers. The properties of Ca2+ sparks observed under control conditions were compared to those measured on depolarized cells and those after caffeine treatment. Calcium sparks were recorded on intact frog skeletal muscle fibers using high time resolution confocal microscopy (x-y scan: 30 Hz). Sparks were elicited by 1 mmol/l caffeine or subthreshold depolarization to different membrane potentials. Both treatments increased the frequency of sparks and altered their morphology. Images were analyzed by custom-made computer programs. Both the amplitude (in ΔF/F0; 0.259±0.001 vs. 0.164±0.001; n = 24942 and 43326, respectively; mean±SE, p<0.001) and the full width at half maximum (FWHM, in µm; parallel with fiber axis: 2.34±0.01 vs. 1.92±0.01, p<0.001; perpendicular to fiber axis: 2.08±0.01 vs. 1.68±0.01, p<0.001) of sparks was significantly greater after caffeine treatment than on depolarized cells. 9.8% of the sparks detected on depolarized fibers and about one third of the caffeine activated sparks (29.7%) overlapped with another one on the previous frame on x-y scans. Centre of overlapping sparks travelled significantly longer distances between consecutive frames after caffeine treatment then after depolarization (in µm; 1.66±0.01 vs. 0.95±0.01, p<0.001). Our results suggest that the two types of ryanodine receptors, the junctional RyRs controlled by DHPRs and the parajunctional RyRs are activated independently, using alternate ways, with the possibility of cooperation between neighboring release channels.